Prevalence of primary ciliary dyskinesia in consecutive referrals of suspect cases and the transmission electron microscopy detection rate: A systematic review and meta-analysis - Kouis, Panayiotis; Yiallouros, Panayiotis K.; Middleton, Nicos; Evans, John S.; Kyriacou, Kyriacos C.; Papatheodorou, Stefania (My University, 2017)
Diagnostic testing for primary ciliary dyskinesia (PCD) usually includes transmission electron microscopy (TEM), nasal nitric oxide, high-speed video microscopy, and genetics. Diagnostic performance of each test should be assessed toward the development of PCD diagnostic algorithms. We systematically reviewed the literature and quantified PCD prevalence among referrals and TEM detection rate in confirmed PCD patients. Major electronic databases were searched until December 2015 using appropriate terms. Included studies described cohorts of consecutive PCD referrals in which PCD was confirmed by at least TEM and one additional test, in order to compare the index test performance with other test(s). Meta-analyses of pooled PCD prevalence and TEM detection rate across studies were performed. PCD prevalence among referrals was 32% (95% CI: 25-39%, I 2 = 92%). TEM detection rate among PCD patients was 83% (95% CI: 75-90%, I 2 = 90%). Exclusion of studies reporting isolated inner dynein arm defects as PCD, reduced TEM detection rate and explained an important fraction of observed heterogeneity (74%, 95% CI: 66-83%, I 2 = 66%). Approximately, one third of referrals, are diagnosed with PCD. Among PCD patients, a significant percentage, at least as high as 26%, is missed by TEM, a limitation that should be accounted toward the development of an efficacious PCD diagnostic algorithm.
Keywords: Primary ciliary dyskinesia; Patients; Children; TEM